Successful use of the Unified Dyskinesia Rating Scale regardless of PD- or dyskinesia-duration. (October 2019) - Ren, Xuehan; Lin, Jeffrey; Luo, Sheng; Goetz, Christopher G.; Stebbins, Glenn T.; Cubo, Esther
Abstract: Objective: We assessed differential item functioning (DIF) in the Unified Dyskinesia Rating Scale (UDysRS) to evaluate bias risk from the duration of Parkinson's Disease (PD) and duration of dyskinesia. Background: Assessing DIF is a core validation step for rating scales. If DIF is present for an item, interpretation must consider influences from the tested covariates. DIF can be uniform or non-uniform, depending on the consistency of influence from the given covariate across all levels of dyskinesia. Methods: Using a large UDysRS database (N = 2313), uniform and non-uniform DIF related to the duration of PD and/duration of dyskinesia were tested. Unidimensionality of UDysRS was first confirmed using confirmatory factor analysis. DIF analysis was conducted using two independent latent models. DIF in an item was confirmed if both methods independently identified DIF at a significance level using Bonferroni correction. McFadden pseudo R^2 measured clinical relevancy of DIF magnitude (negligible, moderate, and large) for items identified with DIF, and items with DIF were considered clinically relevant if they exceeded a negligible designation. Results: Most items did not show uniform or non-uniform DIF based on PD and dyskinesia duration in isolation or in combination. For all items where DIF was identified, the magnitude statistic was in the negligible range (McFadden pseudo R^2 < 0.035) and the combined impact of multiple identified DIF items on UDysRS likewise did not exceed the negligible designation. Conclusion: The absence of clinically relevant DIF suggests that the UDysRS can be applied across all patients regardless of their PD- or dyskinesia-duration. Highlights: We assessed differential item functioning (DIF) in the UDysRS. Most items did not show DIF based on PD and dyskinesia duration. The items with DIF showed a clinically negligible effect. PD and dyskinesia duration do not influence UDysRS measuring dyskinesia severity. UDysRS can be used confidently in populations with varying PD and dyskinesia duration.